Association between temporomandibular disorders with clinical and sociodemographic features: An observational study - Delgado Delgado, Raquel; Iriarte Álvarez, Naiara; Valera Calero, Juan Antonio; Centenera Centenera, Belén; Garnacho Garnacho, Victoria Eugenia; Gallego Sendarrubias, Gracia María (My University, 2021)
Background: Temporomandibular disorders (TMD) are the most common orofacial impairment, but the relevance of certain clinical features in TMD is not clear. Objective: The main objective of this study was to analyse if temporomandibular disorders (TMD) are associated with sociodemographic (eg age, height, weight, body mass index and gender), psychological (eg anxiety and depression) and clinical fea tures (eg use of dental splints, orthodontics, retainers, bruxism, sleep disturbance, familiar prior history of TMD and dental occlusion). Methods: An observational study was conducted to calculate the correlation of TMD, as assessed with DC/TMD criteria, with sociodemographic, psychological and clinical features on 59 voluntary subjects with TMD (n = 45) and without TMD (n = 14). Sex, height, weight, body mass index, age, use of dental splint, orthodontics, retainers, parafunctional disorders, sleep disturbance, familiar history of TMD, bruxism, anxi ety, stress and dental occlusion class data were included in a multivariable correlation analysis to determine which variables are associated with TMD and bruxism. Results: TMD was found to be correlated with none of the features assessed (P > .05), but a negative correlation with the use of dental splint (P < .05). Dental occlusion class showed no statistically significant correlation with any assessed feature (P > .05). Conclusion: The etiology of TMD is not clear and considering certain clinical features including dental occlusion are not justified in the evidence-based TMD practice for making irreversible occlusal treatment decisions